Open Educational Resources and the Opportunities for Expanding Open and Distance Learning (OERS-ODL) - Mbale, Jameson; Egan, Jack; Frindt, T (International Journal of Emerging Technologies in Learning (iJET), 2013)
Distance learning (DL) was a teaching modality which utilized technology to deliver teaching to students who were not physically present such as in a traditional classroom setting. DL was not constrained by geographic considerations and therefore offered unique opportunities to expand educational access. The University of Namibia (UNAM) and International Training and Education Center for Health (I-TECH) partnered to examine DL at UNAM, to assess strengths and weaknesses, and to make recommendations for improvement. The primary method used in this assessment was interviews with staff at centers and units engaged in Distance Learning at UNAM. It was analyzed how interactions vary between instructor and learner, among learners, and between learners and learning resources. DL at UNAM was categorized into five approaches including: 1) Outreach, 2) Print-based, 3) Computer based, 4) Internet-based, and 5) Digital Video Conferencing (DVC). All-in-all, a strategy of â??starting smallâ? was envisaged to allow individual instructors to voluntarily use collaborative software such as Google Groups to enhance print-based instruction and progressively expand DL at UNAM.